Invariantes geométricos de pares de curvas planares - Pádua, Nathanni Vieira de (2020)
The objective of this work is to study the affine invariants, by affine transformations, projective invariants, by projective transformations, and conforming invariants, by Mobius transformations, for certain pairs of curves. Basically we will have these three cases: pair of plane curves having a tangent in common at the two points of quadratic tangency, pair of plane curves intersecting at a common point, and finally, pair of tangent plane curves at a common point.